Improved inductive-system-level IEC ESD performance for automotive applications using mutual ballasted ESD protection technique. (February 2016) - Salman, Akram A.; Farbiz, Farzan; Concannon, Ann; Edwards, Hal; Boselli, Gianluca
Abstract: A new ESD failure mode under inductive IEC stress of automotive Controller Area Network (CAN) bus is identified. Inductor saturation causes increase of the rise-time from 1 ns to ~ 20 ns, leading to non-uniform conduction in the bidirectional ESD protection circuit. A novel mutual ballasting layout technique is introduced to recover the system level ESD performance. Highlights: Inductive IEC ESD stress causes unexpected damage. Damage is due non uniformity of conduction with slow risetime. Window failure can occur under this condition. Mutual ballasting layout technique improves performance dramatically. Minimal impact on the area of the ESD cell